A review of the Oriental species of Cothornobata Czerny (Diptera, Micropezidae, Eurybatinae) - Li, Xuankun; Marshall, Stephen A.; Yang, Ding (Zootaxa, 2015)
The Oriental species of the genus Cothornobata Czerny are reviewed, with a revision of the species occurring in the northern Oriental region, and descriptions of the following 16 new species from China and Vietnam: C. atra sp. nov.; C. breviseta sp. nov.; C. bubengensis sp. nov.; C. curva sp. nov.; C. elegantula sp. nov.; C. fusca sp. nov.; C. ingensfurca sp. nov.; C. longifurca sp. nov.; C. longigonitea sp. nov.; C. mentogensis sp. nov.; C. paieroi sp. nov.; C. pugnoa sp. nov.; C. shuimanensis sp. nov.; C. uniseta sp. nov.; C. vietnamensis sp. nov.; C. zhangae sp. nov. Cothornobata nigrigenu Enderlein is newly reported from China and Nestima meijerei (Frey) is given as a new combination for Cothornobata meijerei Frey. A key to the 19 Oriental species of the genus is provided.